Fault-controlled geomorphic features in Ridi-Shantipur area of Gulmi District and their implications for active tectonics - Timalsina, Kumar; Paudyal, Kabi Raj (Journal of Nepal Geological Society, 2018)
The Lesser Himalaya is a fold-thrust belt in the Himalaya. In the Nepal Himalaya, several active faults, among which the Badi Gad Fault is one of them, are identified and mapped by many researchers in the past, However, very less study has been carried out on the existence of this fault and its extension. In the present study, an attempt was made to assess the fault and to map its extension in the region based on the geological as well as geomorphological criteria. For this purpose, a detailed geological map was prepared from Ridi to the Shantipur area in 1:25,000 scales. During the field work, several geological as well as geomorphic evidences of the existence of active fault were found, and some of them are also found under the aerial photo observation. These evidences include the presence of shear zones, clustering of large and several landslides along a confined linear zone, river course diversion, terrace tilting, fault scarps etc. In the present work, the Badi Gad Fault is traced out continuously from the Ridi to the Shantipur area and even extended far to the NW direction under aerial photo. The fault follows the moderate hills of the left bank of the present course of the Badi Gad River. Major shear zones found in the region are the Tal Khola, Aslewa, Eksingaun, Juhan, Gultung, and the Rupakot shear zones. These shear zones are represented by the wide zone of fault gauge, fault breccias, silickensides, striations and large landslides. Besides, other geomorphic evidences traced out are location of spring lines, tilted river terraces in Pul Camp and Wamitaksar area, river course diversion of the Lumdi Khola and fault scarp at Bhanjyangaun of Aslewa. Such types of fault-controlled geomorphic features are also found from the Rudrabeni-Wamitaksar areas under the aerial photos. Based on the fault controlled geomorphological study in the field and aerial photos interpretation, an attempt was made to map the Badi Gad Fault, an active strike slip fault in the region.